1990
DOI: 10.1152/jappl.1990.68.2.554
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects of compression rate and duration in cardiopulmonary resuscitation

Abstract: The effects of various compression rate and duration combinations on chest geometry and cerebral perfusion pressure during cardiopulmonary resuscitation (CPR) were studied in immature swine. Pentobarbital-anesthetized 2- and 8-wk-old piglets received CPR after ventricular fibrillation. At compression rates of 40, 60, 80, 100, 120, and 150/min, duty cycle (compression duration/total cycle time) was increased from 10 to 80% by 10% increments. Mean aortic and sagittal sinus pressures, pulsatile displacement, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…The concept of ACD CPR is further supported by the fact that the juvenile chest wall lacks an intrinsic tendency to rebound when released from compression during CPR. As such, Dean et al (13) demonstrated that inadequate chest recoil, development of static chest deforma- tion, and limitation of pulsatile chest wall movement occurred in 8-wk-old pigs when relaxation time was as short as 250 -300 ms during CPR. Because venous blood return to the chest and diastolic right atrial pressure are highly dependent on the intrathoracic pressure drop during the relaxation phase of CPR, we suggest that ACD ϩ ITV CPR in pediatric patients may even contribute more than in adults to the concept of enhancing the bellowslike action of the chest.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ACD CPR is further supported by the fact that the juvenile chest wall lacks an intrinsic tendency to rebound when released from compression during CPR. As such, Dean et al (13) demonstrated that inadequate chest recoil, development of static chest deforma- tion, and limitation of pulsatile chest wall movement occurred in 8-wk-old pigs when relaxation time was as short as 250 -300 ms during CPR. Because venous blood return to the chest and diastolic right atrial pressure are highly dependent on the intrathoracic pressure drop during the relaxation phase of CPR, we suggest that ACD ϩ ITV CPR in pediatric patients may even contribute more than in adults to the concept of enhancing the bellowslike action of the chest.…”
Section: Discussionmentioning
confidence: 99%
“…A compression to relaxation ratio with a slightly shorter compression than relaxation phase offers theoretical advantages for blood flow in the very young infant. 64 Keep the thumbs or fingers on the sternum during the relaxation phase.…”
Section: Compression Techniquementioning
confidence: 99%
“…KPR süresi uzadıkça göğüs kompresyon kalitesi kötüleşir ve buna bağlı komplikasyon olasılığı artar (8,9). Süresi uzayan KPR' ye bağlı intra abdominal komplikasyonlar meydana gelebilir (10).…”
Section: Olgu Sunumuunclassified